Hypermogins A–D, four highly modified polycyclic polyprenylated acylphloroglucinols from Hypericum monogynum. (2nd February 2021) - Zeng, Yanrong; Yang, Jue; Li, Yanan; Gu, Wei; Huang, Liejun; Yi, Ping; Yuan, Chunmao; Hao, Xiaojiang
Graphical abstract: Highlights: Four new polycyclic polyprenylated acylphloroglucinols were isolated from Hypericum monogynum . Hypermogins A–D (1 –4 ) were characterized by an unusual 6, 5, 5-tricyclic system. All compounds exhibited significant reversal activity on MCF-7/ADR. Abstract: Four highly modified polycyclic polyprenylated acylphloroglucinols (PPAPs) with an unusual 6, 5, 5-tricyclic system, hypermogins A–D (1 –4 ), together with one known analogue (5 ), were isolated from the flowers of Hypericum monogynum . From a possible biogenic synthesis pathway analysis, compounds 2 and 3 could be obtained by oxidation of a double bond and hydrolysis for 1 and 5 . In addition, compound 3 might undergo a pinacol rearrangement to produce compound 4 . The structures of the isolates were determined by comprehensive MS, NMR spectroscopy and electronic circular dichroism (ECD) calculations. All compounds significantly reversed multidrug resistance in MCF-7/ADR cells.